Land Use Classification of Al-Rifai City Manually and Using Google Earth - Chlaib, Hussein; Adil Mohammed, Fatmah; Abd Yasir, Najem Abd; R. Zachi, Hakeem (University of Thi-Qar Journal of agricultural research, 2025)
The research dealt with a manual classification of land uses in Al-Rifai area using (220) satellite images taken from Google Earth and captured at an altitude of 831 m. Each image was divided into squares with dimensions of 2 cm x 2 cm, which equals to 0.2 km2 as an actual area. Red color represents to residential (urban) lands, green color represents agricultural lands, and brown color represents barren lands, while water areas were colored blue. Through the manual classification of land uses in the areas located within the administrative boundaries of Al-Rifai city, with a total area of ​​1610 km2, it became clear that the areas of residential areas were approximately (763) km2 with a percentage of (47.39%), agricultural areas were approximately (555) km2 with a percentage of (34.47%), barren areas were approximately (263) km2  with a percentage of (16.33%), and water areas were approximately (29) km2  which equals about (1.80%). Using the drawn color map, it can be predicted that the agricultural areas (green), located in scattered patches between residential areas (red), could shrink due to population growth and family division.